Analysis of the Application of Circular Economy Concepts in Coffee Shop Business - Muhammad Rafli; Asiroch Yulia Agustina; Nur Khayin Muhdlor (Innovation Business Management and Accounting Journal, 2025)
This research aims to analyze the application of circular economy principles in the coffee shop business as a step towards creating a sustainable business model. The concept of circular economy focuses on resource optimization by applying the 3R principles (Reduce, Reuse, Recycle) and reducing dependence on limited natural resources. The approach used in this research is descriptive qualitative, through case studies in several coffee shops that have adopted environmentally friendly practices, such as the utilization of recycled materials, processing coffee waste, and reducing the use of single-use plastics. Data collection was conducted through in-depth interviews, direct observation, and documentation tasks. The findings from this study show that implementing a circular economy can improve operational efficiency, create a positive image in the eyes of consumers, and provide both economic and environmental benefits. Although there are some challenges, such as high start-up costs and a lack of business and consumer awareness, the strategy is considered to have the potential to be implemented more widely. The hope of this research is to contribute to small and medium enterprises in developing businesses that are not only financially profitable, but also contribute to environmental conservation.